DEVELOPING DAR APPLICATION BASED ON ANDROID IN READING ENGLISH TEXT - Nisa, Choirun; Bahtiar, Yuyun (Universitas Nias Raya, 2023)
The purpose of this research was to develop DAR (Descriptive, Announcement, and Recount Text) Application Based Android in Reading English Text for Senior High Students in grade X. The researcher used Research and Development (R&D) method and adapted ADDIE (Analyze, Design, Development, Implementation, and Evaluation) models. Based on the resulting development the researcher got a result of media validation 95,8% scores, which was the “very good” category. In the material validation, the researcher got 92,1% scores, which was a “very good category”, and in the result of product implementation, the researcher got 92,1% scores, which was a “very good” category. From those data, it can be concluded that DAR Application was feasible as a learning media in teaching-learning English.